Analysis of Mathematical Problem-Solving Ability Materials on the Volume of Building Spaces in Class V Students of SDN 176 Palembang (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
Problem-solving is a process or individual effort to respond or overcome obstacles or obstacles when an answer or answer method is not yet clear. This means that problem solving can make students create new ideas or techniques in a problem. Based on this, the problem in this study is how the mathematical problem-solving ability of students in the volume of space in the fifth-grade students of SDN 176 Palembang is solved. The purpose of this study is to determine and describe the mathematical problem-solving abilities of fifth-grade students in the volume of building materials. The results showed that the mathematical problem-solving ability (1) students were in high category, students were able to understand the problem correctly, were able to make a were able to carry out the appropriate stages of the problem-solving ability indicator correctly, able to make conclusions answers obtained. (2) moderate category students, students can carry out problem-solving steps such as planning to solving problems. (3) low category students, students cannot find out the problem and carry out problem-solving steps according to indicators such as planning, solving problems and making conclusions from the answers.